Absolute Configuration and Biological Activities of Meroterpenoids from an Endophytic Fungus of Lycium barbarum - Long, Yi; Tang, Ting; Wang, Li-Ying; He, Bin; Gao, Kun (Journal of natural products (Washington, D.C.), 2019)
Eleven new meroterpenoids, bipolahydroquinones A–C (1–3), cochlioquinones I–N (4–8 and 11), and isocochlioquinones F and G (9 and 10), together with six known ones, were obtained from an endophytic fungus Bipolaris sp. L1-2 from Lycium barbarum. Compound 2 is the first example of cochlioquinone derivatives possessing a benzofuran moiety. The structures and absolute configurations of the new compounds were elucidated by spectroscopic data interpretation, single-crystal X-ray diffraction analysis, chemical transformations, and biosynthetic considerations. Compounds 3, 4, and 6–8 showed cytotoxicity against NCI-H226 and/or MDA-MB-231 with IC50 values ranging from 5.5 to 9.5 μM.